2011
DOI: 10.1021/jp2100717
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Multiple Protonation on the Initial Excitation in a Black Dye

Abstract: Solvent pH influences electronic and optical properties of photoactive systems by protonation/deprotonation of basic/acidic positions. In this study a joint experimental and theoretical approach is presented to analyze the acid/base properties of a new 4H-imidazole ruthenium(II) complex (Ru). The imidazole ligand is substituted by two dimethylamino groups and hence offers four positions for protonation. To identify the species present in certain acid concentration ranges calculated absorption and resonance Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 98 publications
2
42
0
Order By: Relevance
“…Due to the direct and strong interaction between each chromophore with the metal center the complexes exhibit the photoelectrochemical and photophysical properties related to the ruthenium(II)polypyridine fragment while displaying broad and strong absorption in the visible range due to the presence of strong 1 MLCT and ligand centered ( 1 LC) transitions. [29][30][31][32][33][34] Furthermore, the redox and photophysical properties of the 4H-imidazole coordinating ruthenium(II) complexes can be easily tuned by varying the substituent pattern and the protonation state of the ligand, as has been recently shown. 30,31,33,34 These properties render complexes like RuIm with promising structures for use as molecular sensitizers in DSSCs, in which the electron injection from the photoexcited light harvesting unit into the wide bandgap semiconductor occurs via an anchoring group, typically a carboxylate group (COO À ).…”
Section: Introductionmentioning
confidence: 95%
“…Due to the direct and strong interaction between each chromophore with the metal center the complexes exhibit the photoelectrochemical and photophysical properties related to the ruthenium(II)polypyridine fragment while displaying broad and strong absorption in the visible range due to the presence of strong 1 MLCT and ligand centered ( 1 LC) transitions. [29][30][31][32][33][34] Furthermore, the redox and photophysical properties of the 4H-imidazole coordinating ruthenium(II) complexes can be easily tuned by varying the substituent pattern and the protonation state of the ligand, as has been recently shown. 30,31,33,34 These properties render complexes like RuIm with promising structures for use as molecular sensitizers in DSSCs, in which the electron injection from the photoexcited light harvesting unit into the wide bandgap semiconductor occurs via an anchoring group, typically a carboxylate group (COO À ).…”
Section: Introductionmentioning
confidence: 95%
“…The theoretically possible double protonation of the imidazole ring was not considered, because it could not be observed for structurally similar 4H-imidazole complexes including Ru2. [10,11] In principle two modes of protonation of Ru1(ImCOO) are possible: The monoprotonated species can occur as Ru1(ImHCOO) with a protonated imidazole ring, or as Ru1(ImCOOH) with a protonated carboxylate group. The first protonation of Ru1(ImCOO) causes a small bathochromic shift of the longwavelength absorption band by 0.03 eV, from 556 to 563 nm.…”
Section: Steady-state Absorption and Protonation Statesmentioning
confidence: 99%
“…In former studies on related 4H-imidazole systems, [10,11,15] resonance Raman spectroscopy [28] revealed its potential to discriminate between forms with nonprotonated and protonated imidazole rings. The resonance Raman spectrum of the monoprotonated species of Ru1 showed almost no signatures of the protonated imidazole ring ( Figure S2).…”
Section: Steady-state Absorption and Protonation Statesmentioning
confidence: 99%
See 2 more Smart Citations